Factors Influencing the Improvement of Indonesian Seafarers' Competency Quality - Arief Rahman; HM Thamrin; Prasadja Ricardianto; Munawaroh Zainal (Green Publisher, 2025)
This study examines key factors that influence the improvement of Indonesian seafarers' competency. Using a quantitative approach, the research focuses on three main areas: training and education, training infrastructure, and technology implementation. A random sampling method was used to gather data from 100 respondents, including active seafarers, new graduates, maritime instructors, and HR managers from shipping companies. Data was collected through questionnaires and analyzed using Multiple Linear Regression with SPSS 25. The results show that all three factors significantly impact the quality of seafarers' competencies. Improvements in training and education, infrastructure, and technology are essential for enhancing skills and ensuring safety at sea. Collaboration between the government, training institutions, and companies is crucial to achieving these improvements and boosting Indonesia’s maritime competitiveness globally.